Functional MRI study of feedback-based reinforcement learning in depression - Kustubayeva, Almira M.; Nelson, Erik B.; Smith, Michael L.; Allendorfer, Jane B.; Eliassen, James C. (Frontiers in Neuroinformatics, 2022)
Reinforcement learning depends upon the integrity of emotional circuitry to establish associations between environmental cues, decisions, and positive or negative outcomes in order to guide behavior through experience. The emotional dysregulation characteristic of Major Depressive Disorder (MDD) may alter activity in frontal and limbic structures that are key to learning. Although reward and decision-making have been examined in MDD, the effects of depression on associative learning is less studied. We investigated whether emotional dysregulation observed with MDD would be related to abnormalities in learning-related brain activity as measured by fMRI. Also, we explored whether melancholic and atypical features were associated with altered brain activity. We conducted MRI scans on a 4T Varian MRI system in 10 individuals with major depressive disorder and 10 healthy subjects. We examined event-related brain activation during feedback-based learning task using AFNI for image processing and statistical analysis. We observed that MDD patients exhibited reduced activation in visual cortex but increased activation in cingulate and insular regions compared to healthy participants. Also, in relation to features of depressive subtypes, we observed that levels of activation in striatal, thalamic, and precuneus regions were negatively correlated with atypical characteristics. These results suggest that the effects of MDD, including emotional dysregulation, change the neural circuitry underlying associative learning, and these effects may depend upon subtype features of MDD.